EFFETS D’UNE TEMPERATURE FRAICHE ET D’UN APPORT EXOGENE DE REGULATEURS DE CROISSANCE SUR DES SEMIS DE CHENE LIEGE - Malika Rached-Kanouni; Fayçal Benmansour; Djamel Alatou (European Scientific Journal, ESJ, 2013)
The seedlings of Cork oak (Quercus suber L.) cultivated in uniform conditions at 25°C for a duration of long day of 16 hours are transferred for a week to a cool temperature of 5°C, to precise morphological stages. After coming back to initial conditions of cultivation, the temporal and spatial modifications are observed on waves. When the seedlings are transferred to “full bloom bud”, the caulinair strength phase last more time, and the component “rest period” is abolished. Concerning the other stages of transfer “swollen bud and rest period”, the duration of rest period and the formation of scales increase with the formation of semi-phase for the first stage. So, some spatio-temporel modifications appear, they are similar to those observed by the application of growth’s regulators of type gibberelic acid at full-bloom bud stage and rest period and cytokinine (kinetic) at swollen stage.